A Class of Nonlinear Integral Operators Preserving Double Subordinations. (11th May 2005) - Kwon, Oh Sang; Cho, Nak Eun
Abstract : The purpose of the present paper is to investigate some subordination- and superordination-preserving properties of certain integral operators defined on the space of meromorphic functions in the punctured open unit disk. The sandwich-type theorem for these integral operators is also considered.